Nephron sparing surgery (NSS) for unilateral wilms tumor (UWT): The SIOP 2001 experience. Issue 12 (23rd August 2014) - Wilde, Jim C.H.; Aronson, Daniel C.; Sznajder, Beata; Van Tinteren, Harm; Powis, Mark; Okoye, Bruce; Cecchetto, Giovanni; Audry, Georges; Fuchs, Jörg; Schweinitz, Dietrich Von; Heij, Hugo; Graf, Norbert; et al.
Abstract Background Total nephrectomy (TN) remains the standard treatment of unilateral Wilms tumors (uWT). The SIOP WT‐2001 protocol allowed Nephron Sparing Surgery (NSS) for polar or peripherally non‐infiltrating tumors. Aim: Inventory of the current SIOP NSS‐experience. Procedures 2, 800 patients with a unilateral, localized or metastatic and an unequivocal surgical technique recorded were included. All had neo‐adjuvant chemotherapy and delayed surgery. In 91 (3%) NSS was performed and in 2709 TN. Data was retrieved from the SIOP WT 2001 database. Results NSS group contained 65% stage I tumours and the TN group 48%. Tumor volume (at diagnosis and surgery) was significantly smaller in the NSS group. Within stage III, after NSS, 7/12 (58%) had positive margins (M +), 5 with tumor negative lymph nodes (LN‐). After TN, 355/712 (55%) had M + , 182 were LN‐. Treatment of M+ in the NSS group resulted in two conversions to TN (one combined with radiotherapy), three patients had radiotherapy only and in two patients local therapy, if given, was not recorded. After NSS, four recurrences occurred. For localized disease the 5‐year overall (OS) and event free survival (EFS) in NSS group was 100 and 94.8 (95% CI:89.9‐99.9), respectively, while OS and EFS in the TN group were 94.4 (95% CI: 93.2‐95.5, log‐rank test P = 0.06) and 86.5 (95% CI:85.0‐88.1, log‐rank test P = 0.06), respectively. Conclusions NSS was only performed in 3% of patients with uWT. Despite excellent survival with few relapses, the gain of nephrons needs to be weighed against the risk to induce stage III with intensified therapy. Pediatr Blood Cancer 2014;61:2175–2179. © 2014 Wiley Periodicals, Inc.